WILAYAH JANGKAUAN PELAYANAN PASAR DI KOTA SAWAHLUNTO - stella carolina; Ahyuni Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This study aims to determine the range of market service coverage, the flow patterns of goods and the market hierarchy in Sawahlunto City. This type of research is quantitative descriptive. Data collection through observation and questionnaire. The population and sample are buyers and traders. Research data were analyzed using the Borgadus Scale and Analysis Buffer. The results of the study: (1) The range of market services: (a)Daily goods: 12,7km (Sawahlunto Market), 7km (Silungkang Market), 10,9km (Talawi Market) and 2km (Sapan Market), (b)Monthly goods: 9km (Sawahlunto Market) 7,9km (Silungkang Market), 7,7km (Talawi Market) and 2km (Sapan Market), (c)Annual goods: 13km (Sawahlunto Market), 5km (Silungkang Market), 7,7km (Talawi Market) and 2km (Sapan Market), (d)Luxury goods: 10,9km (Sawahlunto Market), 2,6km (Silungkang Market), 0,7km (Talawi Market) and 0,5km (Sapan Market). (2) The flow of goods: (a)Sawahlunto Market (Bukittinggi City, Solok City and Padang City), (b)Silungkang Market (Bukittinggi City and Solok City), (c)Talawi Market (Tanah Datar District and Bukittinggi City), (d)Sapan Market (Padang City and Bukttinggi City). (3) Sawahlunto Market (City Market), Talawi Market (Regional Market) Silungkang Market and Sapan Market (Environmental Market).